Networked digital technologies Third International Conference, NDT 2011, Macau, China, July 11-13, 2011. Proceedings - Fong, Simon (Communications in Computer and Information Science, 2011)
This book constitutes the proceedings of the Third International Conference on Networked Digital Technologies, held in Macau, China, in July 2011. The 41 revised papers presented were carefully reviewed and selected from 127 submissions. The papers are organized in topical sections on information security, networks, information management, multimedia, human computer interaction and simulation, e-learning and e-government, Web services/semantics, user centric information system/intelligent computing, and data mining.